Study Protocol of the Endobronchial VAlves for Pneumothorax to Reduce Admission Time ( EVAPoRATe ) Pilot Multicentre Randomised Clinical Trial - Nai‐Chien Huan; Niranjan Ananda Setty; Ai Ling Tan; Dhaval Thakkar; Taha Huseini; Elaine Yap; Jonathan Williamson; Phan Nguyen; Paul Lilburn; Matthew Salamonsen; Arash Badiei; Matthew Ing; et al. (Respirology Case Reports, 2026)
ABSTRACT Background Pneumothorax with persistent air leak (PAL) is a debilitating condition. Patients with PAL often require prolonged chest drainage, with associated complications, such as, hospital‐acquired infections, thromboembolism, and deconditioning. Endobronchial valves (EBVs) are an approved bronchoscopic treatment for PAL and may allow earlier chest tube removal and hospital discharge. Current evidence supporting the use of EBV is limited to case series and uncontrolled studies. EBVs are usually used as a last resort when other treatments failed. Whether early referral for EBV placement is feasible and can reduce hospital length of stay in patients with pneumothorax and PAL has not been tested in a randomised controlled trial (RCT). Methods EVAPoRATe is a prospective, open‐labelled, pilot, multi‐centre RCT. Forty patients with pneumothorax of any cause and PAL who are unsuitable for or unwilling to undergo surgical management will be randomised 1:1 to the Early EBV Referral arm or the Standard Care arm. Patients in the Early EBV Referral arm will be assessed by an interventional clinician for EBV placement at the earliest feasible time from Day 5 of pneumothorax. Patients allocated to the Standard Care arm will receive conventional management by the attending team; EBV is allowed if clinically appropriate when air leak persists after 12 days. Participants will be followed for 6 months after discharge. Discussion The primary outcome is the feasibility of the trial protocol, assessed by recruitment rate, adherence to the intervention arm, and retention at follow‐up. Secondary outcomes include total hospital length of stay, PAL‐related length of stay, interventions for PAL and EBV complications, time to air leak cessation, time to chest drain removal, pneumothorax recurrence, adverse events and serious adverse events, removal of EBVs, performance status, and mortality. This pilot feasibility study will assess whether a future full‐scale RCT of EBV for PAL is practical and will provide data to guide protocol refinement and sample size calculation. Trial Registration Australian New Zealand Clinical Trials Registry: ACTRN12625000360415; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=388086&isReview=true